Can an inhibitor of a multidrug pump become a substrate? - Hutchison, Ella (2022)
ABCG2 is an ATP binding cassette (ABC) transporter that is involved in multidrug resistance, particularly anti-cancer drugs such as methotrexate and mitoxantrone. Distinguishing between substrates and inhibitors is important for rational design of drugs that won’t be transported by ABCG2 and inhibitors that prevent transport of existing ABCG2 substrates. In this project, the hypothesis being proposed is that ligands with a higher affinity for ABCG2 act as inhibitors and the transient conformational changes required for transport do not occur. Whereas transported substrates have a lower affinity for ABCG2 and the conformational changes can occur. Therefore, if the affinity for a widely used inhibitor, Ko143, was reduced, would it become a substrate that is transported by ABCG2? A series of mutants (T435A, N436A, F439A, S440W, M549E, A397S/V401A/L539A and L405A/I543A/V546A) were designed using cryo-EM structures of ABCG2 bound to MZ29 (a Ko143 analogue) and mutational studies of substrate transport. The aim was to reduce affinity of ABCG2 for Ko143. All mutant proteins, except M549E, were successfully expressed in HEK293T cells and trafficked to the cell membrane. Using flow cytometry, cellular accumulation of fluorescent Ko143 derivatives (Ko143-Cy5 and Ko143-X-BY630) was measured which indicates whether they are exported by ABCG2 or not. Ko143-Cy5 fluorescence was significantly higher in WT-ABCG2 expressing cells compared with the untransfected control and the other ABCG2 mutants, except for A397S/V401A/L539A. Ko143-X-BY630 showed a similar pattern but without significance. The reduction in cellular accumulation of the fluorescent Ko143 derivatives in the mutants could be caused by the reduced affinity leading to ABCG2-mediated transport or increased diffusion out of the cell. Transport of Ko143-Cy5 or Ko143-X-BY630 cannot be ruled out but it is not detectable in this experiment. Consideration of the data in this thesis alongside emerging structural and functional data from other laboratories will continue to shed light on the interaction of substrates and inhibitors with ABCG2.